Edukasi Kenakalan Remaja Pada Anak Usia Dini Di Yayasan Samiyah Amal Insani - Fihra Rizqi; Muhammad Novaldy; Nico Ilham; Muhammad Ramadhan S; Nabilah Azhari Putri Rahmatullah; Muhammad Fadhail; Irsyad Rahmatan (Doktrin:Jurnal Dunia Ilmu Hukum dan Politik, 2023)
Since a long time the problem of juvenile delinquency is very worrying. Because at that time teenagers began to look for identity so that teenagers chose despicable paths. In fact, it often happens that teenagers take actions that result in breaking the law. And also teenagers don't know that the actions they take have risks without them knowing it. So that it is fatal for himself and others. The purpose of this service is to provide them with an understanding so that they know more about themselves in their teens and provide an understanding of what is youth? And what are examples of juvenile delinquency and the consequences arising from the actions that teenagers do. so that when entering their teens they do not commit delinquency which results in harming themselves. This counseling activity was carried out with lectures and questions and answers by providing pre text and post text, which was held in collaboration with the Samiyah Amal Insani Foundation, Bandung City, the implementation of the activity was attended by the foundation's children and the results of the counseling showed a significant increase in information law knowledge and electronic transactions